Uji Ketahanan Beberapa Varietas Padi terhadap Patogen Blas (Pyricularia oryzae) - anshari, irwan (Fakultas Pertanian Universitas Tanjungpura, 2021)
Blas disease caused by P. oryzae fungus is one of the main diseases that attack rice crops in Indonesia, Blas disease was previously known to attack gogo rice only Currently the blas disease spread of and already attacked rice fields. The research aims to test the resistance of some rice varieties to blas disease (P. oryzae). The rice varieties used are Pandan Wangi, Ketupat, Pulut Putih, Inpari 32, and Ciherang. Pathogen inoculation is carried out by spraying konidia suspense and pure breeding. The attack of blas disease pathogen on Ciherang rice varieties is the highest reaching 46.67% - 100% (spray and paste) and the lowest attack 0% on rice varieties of rice fields (fragrant rice, white pulut, and ketupat), after the onset of symptoms is calculated at 6-10 days after inoculation.